Intra- and interpersonal emotion regulation are altered in individuals with childhood maltreatment: cross-sectional associations and effects on daily life mood - Niedtfeld, Inga; Schmitz, Sara E.; Langenstein, Michelle; Hepp, Johanna (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Childhood maltreatment (CM) is a potent predictor of lifelong emotional and psychological difficulties. We investigated how CM affects intra- and interpersonal emotion regulation (ER) processes and explored the impact of these ER difficulties on daily life mood.
Gesehen am 16.09.2025